The emotions in the legislative treatises of Philo and the conceptions of the Stoic legacy (Circe de clásicos y modernos, 2024)
From the problematic of the question of emotions in legislative treatises of Philo of Alexandria, and its relation to the Stoic legacy, our study aims to investigate areas little explored by academic research. On the one hand, it seeks to analyze the definition of páthos in Philo’s legislative treatises, especially in Spec. 4.79. On the other hand, it attempts to examine the classification of emotions in these treatises, reflecting on the affective representation within the framework of the theory of voluntariness (Decal. 142) and of the good and bad values, present and future, of the goods (Decal. 142-146). With this, it intends to contribute to the dialogue on the issue of emotions in the field of Philonic studies and, through this, of Greek Antiquity.
Keywords: emotion; legislative treatises; Stoics; Philo